Grain marketing policy changes and spatial efficiency of maize and wheat markets in Ethiopia - Negassa, Asfaw; Myers, Robert J.; Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 2004)
In the context of on-going market reform in developing countries, there is a need for an improvement in the existing methods of spatial market efficiency analysis in order to better inform the debate toward designing and implementing new grain marketing policies, institutions, and infrastructure that facilitate the emergence of a well developed and competitive grain marketing system. The standard parity bounds model (PBM), while it overcomes many weaknesses of the conventional methods of spatial market efficiency analysis, it does not allow for the test of structural changes in spatial market efficiency as a result of policy changes. In this paper, building on the standard PBM, we develop an extended parity bounds model (EPBM). The EPBM is a stochastic gradual switching model with three trade regimes. The EPBM is estimated by maximum likelihood procedure and allows for tracing the time path and structural change in spatial market efficiency conditions due to the policy changes. We applied the EPBM to analyze the effect of grain marketing policy changes on spatial efficiency of maize and wheat markets in Ethiopia. The results show that the effect of policy changes on spatial market efficiency is not significant statistically in many cases; there is high probability of spatial inefficiency in maize and wheat markets before and after the policy changes. The implication of these results is that maize and wheat markets are characterized by periodic gluts and shortages, which can undermine the welfare of producers, grain traders and consumers. It is also observed that the nature of spatial inefficiency for maize and wheat markets is different implying that the two commodities might require different policy responses in order to improve spatial market efficiency. Maize traders made losses most of the time while wheat traders made excess profits most of the time covered by the study. -- Authors' Abstract